Superficial Effects of Ball Burnishing on TRIP Steel AISI 301LN Sheets - Ramón Jerez-Mesa (Metals, 2021)
This paper explores the consequences of applying an ultrasonic vibration-assisted ball burnishing process and its non-vibration assisted version on the topology and subsurface microstructure of a transformation-induced plasticity AISI 301LN alloy. More specifically, four different metallographic conditions provided as 1.5-mm thickness sheets and characterized by different starting martensite content (3, 10, 20 and 40 wt.%) are included in the study. Ball burnishing was performed along the lamination direction and perpendicular to it. Results show that the effect of ball burnishing is strongly correlated with the pre-existing microstructure. The steel containing the lowest quantity of initial martensite is the most affected by the process, achieving a higher residual hardening effect, similar to the untreated steel with an original martensitic content of around 40 wt.%. Moreover, the process succeeds in generating a 100-nm thick nanograin layer under the plate subsurface. Finally, no conspicuous effect of the application of vibration assistance was observed, which encourages the application of alternative measurement techniques in future works to define its effect on the properties after being ball burnished.